IMAGE DIGITIZATION COLORIMETRIC DETECTION OF ACEPHATE BASED ON ACEPHATE-THIOLATED ACEPHATE BINDING APTAMER-GOLD NANOPARTICLE COMPLEX - Mohd Junaedy Osman (Tesis, 2022)
For years, organophosphates (OPs) compound are used for pest control in agriculture. The detection of OPs using conventional methods gives good results but existed with the several limitations such as bulky, time consuming analysis and expensive. A colorimetric detection method receives an attention as it can be modified to overcome these limitations due to its implicity. In this study, colorimetric detection of Ac was conducted by surface functionalisation of gold nanoparticles with thiolated acephate binding aptamer (TABA). Ultra-violet visible (UV-Vis) analysis showed the existent of surface plasmon resonance phenomenon for both prepared AuNPs whereas Fourier transformed infra-red spectometer (FTIR) analysis suggested there was a physical interaction at the surface of AuNPs.